Calcific pericarditis strangling the heart, an answer to unexplained heart failurediagnostic modalities - Sondang Jasmine Sitorus,; Gede Rur Us Suryawan,; Rosi Amrilla Fagi, (Journal of the Pakistan Medical Association, 2024)
Pericardial calcification is often found incidentally from imaging studies and may be a clue to constrictive pericarditis. Constrictive pericarditis often mimics other causes of heart failure, pulmonary, or liver disease, making it hard to diagnose. Tuberculosis is the most common infectious aetiology of Constrictive Pericarditis. Living in developing countries, such as Indonesia, should warn us of the possibility of tuberculous constrictive pericarditis as a differential diagnosis of unexplained heart failure. The presented case came with complaints of shortness of breath, especially on exertion for five years, which worsened in the last 6 months. The past history of pulmonary Tuberculosis with the Cardiac CT findings confirmed the diagnosis of Constrictive Pericarditis. Keywords: Pericarditis, Tuberculous, Heart Failure, Liver Diseases